Congenital pseudoarthrosis of the clavicle: a case report - Dhungel, K; Ahmad, K; Sah, PL; Gupta, MK; Rauniyar, RK; Ansari, S; Adhikary, S (Journal of College of Medical Sciences-Nepal, 2013)
DOI: http://dx.doi.org/10.3126/jcmsn.v8i3.8687 Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-3, 43-46